Retirement? What Retirement? - Jayne Treasure (The Journal of Classics Teaching, 2016)
Having decided to leave Haberdashers’ Monmouth School for Girls (HMSG) after 23 years in 2013, most of my former colleagues were under the impression that I was planning to retire. To an extent that was true; I did decide to take my teachers’ pension early after a talk about pensions on an INSET day a couple of years earlier (and here I must apologise to younger teachers for whom this may not be a choice). There were some startling statistics about retirement age and the likelihood of death if left too late. Someone suggested it was probably a ruse by the governors to get rid of expensive teachers. If so, it worked. As far as I was concerned, it was one of the most worthwhile INSET days during my career.